Once upon an ordinary school day - McNaughton, Colin (Farrar Straus Giroux, 2004)
Colin's day started out like every other day - his breakfast was ordinary, his walk to school was ordinary, even his thoughts were ordinary. But the new teacher at school changed all that when he told the class about an extraordinary idea. A celebration of extraordinary teachers! The boy's breakfast is ordinary, his walk to school is ordinary, even his thoughts are ordinary. But when he goes to his classroom and sits down at his desk, his day begins to change - a new teacher, Mr. Gee, bursts into the classroom with an extraordinary idea that challenges all the children to use their imagination. Suddenly an ordinary day is turned topsy-turvy, and the boy is inspired in a way that will change him forever. The rollicking words and pictures celebrate the unexpected in this tribute to great teachers and students everywhere.